A Simplified but Comprehensive Laboratory Curriculum for Microbiology in Nursing and Allied Health (MINAH) Courses - Brynn McCall; Anne F. Pacitti; Brian M. Forster (Journal of Microbiology & Biology Education, 2019)
Some U.S. nursing programs have considered or already have removed microbiology courses from their curriculum. In response to this, the American Society for Microbiology (ASM) published in 2018 the Microbiology in Nursing and Allied Health (MINAH) Undergraduate Curriculum Guidelines. Parts of these guidelines include competencies and skills, which are best taught in a laboratory setting. Recognizing that some programs face a burden of running nursing/allied health microbiology lab classes, we have designed a curriculum of seven laboratories that covers the concepts in the MINAH guidelines. These labs cover aseptic technique and proper specimen collection, microscopy, enumerating microorganisms, and diagnostic tests in identifying unknowns. In addition, we provide some tips and tools for keeping down the costs of offering a microbiology lab. It is our goal that these tips and the suggested guidelines will allow microbiology to remain in the nursing and allied health curriculum.